Investigating Teachers’ Attitudes Towards Implementing Drama Activities in the Algerian Secondary School Textbooks A Case Study: Second Year Textbook “Getting Through” - ZAABAB, Farouk ZAABAB (Journal of Human Sciences, 2019)
Competency in English is crucial in a globalized world. Therefore, in a secondary school setting, English courses do not focus solely on the development of the four language skills. Rather, they put emphasis on the application of the English language in real world contexts, and this is known as the Competency Based Approach (CBA).The present paper will investigate the potential use of drama activities in teaching English in the Algerian secondary school. More precisely, focus is placed on the Second Year textbook entitled “Getting Through”. Finding out if and to what extent drama activities will be used by the teachers and what they may think of them is one of our aims. Another equally significant aspect of this paper is to investigate how teachers think about the textbook “Getting Through” and how it can be adapted. To achieve these aims, we administered a teachers questionnaire and designed a Drama Adaptability Checklist. The questionnaire is aimed at a group of secondary school English language teachers, while the Drama Adaptability Checklist is used to analyse the textbook “Getting Through” (second year textbook). The results confirm the hypothesis that teachers have positive attitudes towards using drama activities in the classroom. However, the results also show that changing the textbook activities into drama activities is both difficult and time-consuming